Techno-economic Model of Multimodal Transport - Poul, David; Gregor, Jiří; Pavlas, Martin; Fan, Yee Van (Univerzitetna založba Univerze v Mariboru, 2024)
With the current effort to reduce transport emissions, the shift in the transport of goods from road to rail or combination is expected on a larger scale. For this shift to have the expected results, it needs to be supported by detailed project planning and calculation. The paper presents the techno-economic model of multimodal transport, focusing on road and rail transport. The model includes a vast database of transport systems for both types of transport. To complete the logistic chain, the model includes the calculation for transfer stations, handling equipment, and other needed parts. The model also includes an economic evaluation allowing analysis of the whole logistic chain of multimodal transport or performing the comparison of individual types of transport.

With the current effort to reduce transport emissions, the shift in the transport of goods from road to rail or combination is expected on a larger scale. For this shift to have the expected results, it needs to be supported by detailed project planning and calculation. The paper presents the techno-economic model of multimodal transport, focusing on road and rail transport. The model includes a vast database of transport systems for both types of transport. To complete the logistic chain, the model includes the calculation for transfer stations, handling equipment, and other needed parts. The model also includes an economic evaluation allowing analysis of the whole logistic chain of multimodal transport or performing the comparison of individual types of transport.
Techno-economic Model of Multimodal Transport
Keywords: techno-economic modelmultimodal transportrail transportroad transportintermodal systemstransfer stationcircular economy; techno-economic modelmultimodal transportrail transportroad transportintermodal systemstransfer stationcircular economy